Los estándares de desempeño docente - Changoluisa Gutiérrez, Doris Patricia (2017)
Even tough living in a developed world, the different activities that teachers should perform, making a lack of knowledge about quality standards. It means, neglect their academic preparation as happens at Unidad Educativa “Mariscal Sucre” Saquisilí parish, Cotopaxi province 2016-2017. For that reason, it purposes as aim to diagnose the teachers’ labor with the application of standards for teachers’ performance in the teaching-learning process through a field research. In order to reinforce the research objective, scientific method was used and as complementary way syntactic method as well. Several investigations were done form primaries resources and surveys were used to collect information, it was aimed to teachers, making the analysis and data interpretation from the information gathered, recommendation and conclusion were displayed as well. Among the results, highlight the minimal application of strategies and teaching methodology that carry out teacher continue using traditionalist methods. In order to overcome those problems and improve the XXI century education. It is needed achieve some standards for teacher performance at Unidad Educativa “Mariscal Sucre”. The project’s impact covers the educational field because it allows knowing standards for teachers’ performance to stablish parameters which point out the level of quality to achieve a good performance according to the profession.